Artificial vision applied to manufacturing process - Luini Leonardo Hurtado-Cortés; John Alejandro Forero-Casallas; Víctor Elberto Ruiz-Rosas (Visión Electrónica, 2021)
This article presents the results of the implementation of artificial vision and image processing projects applied to a parts manufacturing process. In a first scenario, three-dimensional computational geometric models of the parts to be manufactured were obtained from the capture and processing of thermo-graphic images. In a later stage of the manufacturing process, a direct measurement system for cutting tool wear was implemented using HD images with image processing software using NI Lab VIEW from National Instruments®. In the final stage of parts manufacturing, the development of software (UDmetaL Handbook) for the quantitative metallographic analysis of micrographs for hypoeutectoid steels is presented. The software determines the type of steel based on the percentage of carbon and finds the mechanical properties of the material in a database that is incorporated into the software. The software's basis of operation is computational analysis through digital processing of metallographic images obtained through experimental laboratory processes using NI Lab VIEW software from National Instruments®.